USE OF YOU TUBE MEDIA IN LEARNING WRITING NARRATIVES IN JUNIOR HIGH SCHOOL STUDENTS - Luluk Setyowati; Irfan Hadi; Mu’thia Mubasyira; Nia Liska Saputri; Sigit Widiyarto (IKIP Siliwangi, 2024)
Learning to write is still considered difficult for some junior high school students. Less than optimal learning and the use of methods that do not pay attention to the situation and abilities of students result in minimal abilities. Teachers are required to innovate and continue to show their creativity in welcoming learning in industry 5.0. This research method uses a pretest post test experimental method in the same class. The number of respondents was 34 class VII students at Kanzul Mubarok Middle School, Bekasi City. The method used in this research is an experimental method with a pre test post test type. The data obtained will be tested for assumptions (homogeneity and normality), and the paired sample t test. Students are able to improve their narrative writing skills through practice and learning sourced from YouTube. Students are expected to be able to develop writing, other than narrative, such as argumentative, descriptive and persuasive writing.